Penetapan Kadar Flavonoid Total Ekstrak Buah Gambas (Luffa acutangula(L.) Roxb.) dengan Metode Spektrofotometri UV-Vis - Suharyanto Suharyanto; Tutik Nur Hayati (Pharmacon: Jurnal Farmasi Indonesia, 2021)
Gambas or Oyong fruit has various benefits, namely it can overcome enlarged lymph nodes, diuretics, laxatives, antioxidants, hepatoprotective, inhibiting the growth of fungi and bacteria. The purpose of this study was to determine the levels of total flavonoid compounds in gambas (Luffa acutangula (L.) Roxb). Extraction methode using soxhletation with 96% ethanol as solvent. The extract obtained was used for qualitative and quantitative analysis. Phytochemical analysis of the flavonoid content in the sample using the Shinoda test, 10% NaOH solution, and concentrated H2SO4 solution, obtained positive results containing flavonoids. Quantitative analysis using UV-Vis Spectrophotometry with the maximum wavelength obtained is 429.5 nm and operating time is 30 minutes. The average total flavonoid content obtained was 9.897±0.11 mg/gram extract with %KV 1.14%.